“Príncipe dos Municípios”: a invenção da identidade de São Caetano do Sul (1948-1957) - Carvalho, Cristina Toledo de (2022)
Entitled “Prince of Counties”: the identity’s invention of São Caetano do Sul (1948- 1957), this thesis proposes the study about the construction of the identity of the São Caetano from the discussion of a set of references, such as representations, memorialistic narratives and places. In the period covered, theses references, which help understanding São Caetano today, represented as a model and developed city, were built and disseminated. The choice of the year of 1948 as the starting point of the period of the research is justified by the fact that the movement in favor of the city’s political autonomy and the stablishment of São Caetano do Sul were observed in it. On the other hand, the year of 1957 showed its relevance as the final mark of the temporality privileged here, since this period was marked as an important episode for the purposes of the research. In the case of the release of the book São Caetano do Sul em IV séculos de história, by José de Souza Martins, this episode brought elements to approach one of the most appreciated issues to the proposed theme: the construction of memories, in the context of the first years of the city life. As the Jornal de São Caetano is its main source, this doctoral thesis unveils the ideals of progress and development on which the image of a victorious and vigorous city was built, a way São Caetano started to reveal itself since 1948. Conversely, the thesis did not avoid criticizing, presenting the other side of that São Caetano of strength and development, marked by a daily life involved in urban problems and by the presence of marginalized people, such as homeless, begging children, northeastern migrants, bootblacks and peddlers